2016
DOI: 10.18632/oncotarget.11515
|View full text |Cite|
|
Sign up to set email alerts
|

Human astrocytes secrete IL-6 to promote glioma migration and invasion through upregulation of cytomembrane MMP14

Abstract: The brain microenvironment has emerged as an important component in malignant progression of human glioma. However, astrocytes, the most abundant glial cells in the glioma microenvironment, have as yet a poorly defined role in the development of this disease, particularly with regard to invasion. Here, we co-cultured human astrocytes with human glioma cell lines, U251 and A172, in an in vitro transwell system in order to ascertain their influence on migration and invasion of gliomas. mRNA and protein expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 39 publications
2
45
0
Order By: Relevance
“…The report then suggests that TAAs in the perivascular niche promote the uPAR‐plasmin cascade to increase MMPs activation in GBM cells, consequently favoring invasion (Figure ). In a similar way, reactive astrocytes have been observed to secrete IL‐6, a protein able to enhance primary GBM cell invasion in vitro (Chen et al, ; Li et al, ). Indeed, GBM development, aggressiveness, and poor prognosis have been linked to the high expression of IL‐6 (Jiang, Han, Cheng, Wang, & Wu, ; Tchirkov et al, ).…”
Section: Role Of Astrocytes During Glioblastoma Developmentmentioning
confidence: 89%
See 1 more Smart Citation
“…The report then suggests that TAAs in the perivascular niche promote the uPAR‐plasmin cascade to increase MMPs activation in GBM cells, consequently favoring invasion (Figure ). In a similar way, reactive astrocytes have been observed to secrete IL‐6, a protein able to enhance primary GBM cell invasion in vitro (Chen et al, ; Li et al, ). Indeed, GBM development, aggressiveness, and poor prognosis have been linked to the high expression of IL‐6 (Jiang, Han, Cheng, Wang, & Wu, ; Tchirkov et al, ).…”
Section: Role Of Astrocytes During Glioblastoma Developmentmentioning
confidence: 89%
“…GAP junctions allow the transfer of cGAMP from glioblastoma cells to surrounding tumor associated astrocytes (inspired by Chen et al, , Chen, Xia, et al, —Servier medical art). Gap junctions established through Cx43 and PCDH7 allow the transfer of cGAMP from GBM cells to TAAs.…”
Section: Role Of Astrocytes During Glioblastoma Developmentmentioning
confidence: 99%
“…Only few experimental studies have analyzed functional roles of astrocytes in GBM biology. These studies have predominantly focused on roles of astrocytes in GBM invasion (Chen et al, ; Le et al, ; Shabtay‐Orbach, Amit, Binenbaum, Na'ara, & Gil, ; Sin et al, ). Other studies have demonstrated interactions between astrocytes and GBM cells affecting drug‐sensitivity of GBM cells, or their response to hypoxia (Chen et al, ; Jin et al, ; Lin, Liu, Ling, & Xu, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, MMP14 is a direct activator of MMP2 (Sato et al, 1994) which can cleave collagen IV, a key component of the basal membranes of epithelial tissues (Halfter et al, 2015). Numerous studies have demonstrated the ability of MMP14 to promote invasion via its catalytic activity (Cathcart et al, 2016;Chen et al, 2016;Macpherson et al, 2014). However, its known functions are not restricted to proteolysis of matrix components in the context of cell migration.…”
Section: Introductionmentioning
confidence: 99%